Predicting the consequences of disperser extinction: richness matters the most when abundance is low. (4th July 2017) - Rumeu, Beatriz; Devoto, Mariano; Traveset, Anna; Olesen, Jens M.; Vargas, Pablo; Nogales, Manuel; Heleno, Ruben
Summary: The ongoing biodiversity crisis entails the concomitant loss of species and the ecological services they provide. Global defaunation, and particularly the loss of frugivores, may negatively affect the seed dispersal of fleshy‐fruited plant species, with predictable stronger impacts in simplified communities such as those on oceanic islands. However, logistical difficulties have hindered the experimental and theoretical need to disentangle the roles of species identity, richness (i.e. number of species) and abundance. Consequently, studies to date have focused exclusively on the loss of species richness leaving us largely ignorant regarding how species identity and abundance affect the loss of ecosystem functions. Here, we applied a network approach to disentangle the effects of disperser abundance, richness and identity on the seed dispersal service provided by frugivores to the Galapagos plant community. We found that both abundance and richness of the dispersers significantly affect the function of seed dispersal and that richness becomes increasingly important as disperser abundance declines. Extinction simulations revealed that the order of species loss has profound implications to the plant community. On the one hand, abundant generalist dispersers like the Galapagos lizards, can mitigate the loss of specialized dispersers. On the other hand, specific threats affecting key dispersers can lead to the rapid collapse of the community‐level dispersal services. Our results suggest that the identity of the disperser species lost can have a large effect on the number of plant species dispersed, and generalist species are essential to the persistence of the community dispersal service. Both abundance and species richness of seed dispersers are key and synergistic drivers of the number of plant species dispersed. Consequently, the coupled negative effect of population declines and species extinctions in frugivore assemblages may lead to an accelerated loss of the seed dispersal function. plain language summary is available for this article. Abstract : Plain Language Summary